SHORT-DISTANCE RUNNING GIRLS WITH VISION DEFECTS TECHNICAL TACTICAL IMPROVEMENT - Tashpulatov, F. A. (Универсальная индексная библиотека Евразийского журнала социальных наук, философии и культуры, 2023)
In this article, a technical tactic for girls short-distance runners with visual impairments information about improvement is given.